Trees in urban religious sites: An analysis of their diversity in Arequipa, Peru - Monteagudo Churata, Lisbeth Yessica (2023)
Facing the trend of rapid urbanization, conserving the biodiversity of urban green spaces is a challenge, particularly in a developing region like Latin America. In this sense, it is known that urban sacred sites have significant cultural and conservation significance within cities. However, more needs to be studied about the vegetation they house. Given the scientific gap, the composition, richness and abundance of trees in urban religious sites of Arequipa established since the 16th century were examined, and temporal changes in the composition and distribution of trees between ancient and modern sites were identified. 749 trees of 54 species were recorded in 26 religious’ sites. A higher proportion of exotic species (74%) corresponds in greater quantity to fruit trees (52%). There were no significant differences in tree richness and abundance between ancient and modern sites. However, the ancient sites had higher richness (96.3%) and abundance (71.4%). Likewise, ancient sites present a preference for growing fruit trees in orchards and cloister gardens, unlike modern sites focused on increasing ornamental trees, with a predominance of conifers and palms. Despite the long history of the monuments, the size of the site and the green areas significantly influenced the richness and abundance; similarly, the care of the gardens greatly influenced a site that stored greater diversity and abundance. In this way, it is demonstrated that these culturally significant places house an important tree diversity, with species of nutritional and ornamental value for the self-provisioning of the religious and the beautification of the gardens. In addition, they contribute to environmental sustainability, providing different ecosystem services to cities with rapid population growth.